2011
DOI: 10.1007/s12275-011-0369-x
|View full text |Cite
|
Sign up to set email alerts
|

A Thermostable phytase from Neosartorya spinosa BCC 41923 and its expression in Pichia pastoris

Abstract: A phytase gene was cloned from Neosartorya spinosa BCC 41923. The gene was 1,455 bp in size, and the mature protein contained a polypeptide of 439 amino acids. The deduced amino acid sequence contains the consensus motif (RHGXRXP) which is conserved among phytases and acid phosphatases. Five possible disulfide bonds and seven potential N-glycosylation sites have been predicted. The gene was expressed in Pichia pastoris KM71 as an extracellular enzyme. The purified enzyme had specific activity of 30.95 U/mg at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Similar results have been reported with the P. pastoris-produced N-glycosylated Bacillus subtilis phytase that shows resistance to trypsin but not pepsin (41). In contrast, the N-glycosylated phytases derived from Aspergillus japonicus BCC18313, A. niger BCC18081, Eupenicillium parvum BCC17694, and Neosartorya spinosa BCC41923 are resistant to pepsin but not to trypsin (26)(27)(28). Our results indicated that the two functional N-glycosylation motifs, NXS/T, of Yersinia phytases contribute to the enzyme proteolytic resistance to pepsin but not trypsin ( Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results have been reported with the P. pastoris-produced N-glycosylated Bacillus subtilis phytase that shows resistance to trypsin but not pepsin (41). In contrast, the N-glycosylated phytases derived from Aspergillus japonicus BCC18313, A. niger BCC18081, Eupenicillium parvum BCC17694, and Neosartorya spinosa BCC41923 are resistant to pepsin but not to trypsin (26)(27)(28). Our results indicated that the two functional N-glycosylation motifs, NXS/T, of Yersinia phytases contribute to the enzyme proteolytic resistance to pepsin but not trypsin ( Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Site-directed mutagenesis has confirmed that the N-glycosylation of scavenger receptor SREC-I at N289 confers resistance against trypsin digestion (25). Some N-glycosylated microbial phytases also exhibit resistance to degradation by pepsin (26)(27)(28). Thus, N-glycosylation represents a stabilizing factor against proteolytic cleavage by proteases (29).…”
mentioning
confidence: 99%
“…Substrate hydrolysis by enzymes in this family occurs via a characteristic two-step mechanism, including a nucleophilic attack of catalytic H on a scissile phosphomonoester and the hydrolysis of a covalent phosphohistidine intermediate with the release of H 15 17 . The optimal activity is usually between pH 1.3–5.5 18 19 and 45–70 °C 19 20 21 , the substrate specificity is diverse 22 and HAP family enzymes display different tolerance to acidity, heat, and proteolytic digestion 23 24 25 26 .…”
mentioning
confidence: 99%
“…LlALP2 contains -Arg-His-Gly-Thr-Arg-Ala-Pro-, the signature peptide in the active site of acid phytases (maximum activity between pH 2 and 6), yet exhibits maximum enzymatic activity at pH 8.0 (the pH in the small intestines) and shows little amino acid sequence similar to acid phytases (approximately 20%) or alkaline phytase from a Bacillus amyloliquefaciens strain (less than 25%) [41], [31]. High-level expression of acid phytases from microorganisms is well documented (for example [23], [33], however heterologous expression of an alkaline phytase from a plant source in amounts necessary for feed studies has been a challenge [45], [16].…”
Section: Introductionmentioning
confidence: 99%